Apelin and heart remodeling in patients with abdominal obesity - O. V. Listopad; E. A. Bazhenova; V. A. Ionin; O. D. Belyaeva; E. I. Baranova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
To evaluate plasma concentration of apelin and its correlation with structural and functional heart parameters in patients with abdominal obesity. 93 patients with abdominal obesity (criteria IDF, 2005) and 21 healthy people at the ages from 25 to 57 years old were investigated. Weight, height, waist circumference, and plasma apelin concentration were measured. Dimensions and volume of the cardiac chambers, systolic and diastolic functions of the ventricles were measured with echocardiographic method. Plasma apelin concentration was higher in patients with abdominal obesity as compared to healthy people (0.70 (0.55 - 0.94) ng/ml and 0.55 (0.42 - 0.72) ng/ml, respectively; p = 0.04). There is significant negative correlation between apelin level and longitudinal size of the left ventricle (r=-0.307; p = 0.003); index of the left atrial volume (r=-0.201; p = 0.05); longitudinal size of the left atrium (r=-0.248; p = 0.02); right atrium volume (r=-0.261; p = 0.01); right atrium area (r=-0,251; p = 0,02); basal size of the right ventricle (r=-0,202; p = 0,05); longitudinal size of the right ventricle (r=-0.234; p = 0.02). Plasma apelin concentration was higher in patients with abdominal obesity as compared to healthy people. There were revealed significant negative correlation between apelin level and longitudinal size of left ventricle, index of left atrial volume, longitudinal size of left atrium, right atrium volume, right atrium area, basal size of right ventricle, and longitudinal size of right ventricle.